PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS KONSUMEN (STUDI KASUS PADA INDUSTRI SUSU BUBUK KEDELAI MELILEA DI KOTA PEKANBARU) - Novia Dewi (Fakultas Pertanian, Universitas Riau, 2014)
The purpose of this study was to know of the marketing mix strategy (product, price, promotion, place) were done of the Melilea soybean milk agroindustry in Pekanbaru and it effect on consumer loyalty of product Melilea. While the methods used in this study is a descriptive analysis to describe of marketing mix data on Melilea soybean milk agroindustry and quantitatif analysis , multiple linear regression analysis, hypothesis testing. Based on the results of analysis of the influence of marketing mix price and marketing channels significantly influence customer loyalty to prepaid Melilea product. It can be seen that the price and markettting channels the most dominant variables influencing consumers decisions Melilea product , the reason being that the product, price and marketing channel has standardized coefficient greater when compared with other standardized coefficient.